The practice of McJournalism in Indonesia’s cyber media - Muslikhin,; Mulyana, Deddy (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to reveal the application of the principles of McJournalism by cyber media in Indonesia. This research has a subjective approach with a constructivist paradigm and uses descriptive qualitative methods. The theory used is McJournalism, which is based on George Ritzer's McDonaldization theory. The sample for this research is Tribunnews.com, an Indonesian cyber media that has the largest network in Indonesia. Data collection was carried out through semi-structured interviews with ten informants, and content analysis of the news published on the website www.Tribunnews.com from December 2020 to January 2021. The implementation of the principle of efficiency was carried out in seven forms. First, the headline uses clickbait. Second, the headline is bombastic, provocative, and lengthy. Third, there are interesting photos in each story. Fourth, one paragraph contains one sentence and the distance between the paragraphs is tenuous. Fifth, the news is distributed through social media by network members. The principle of calculation is carried out by producing as much news as possible. In one day 700 to 1000 news stories are produced, which have high human interest news value and the ability to be shared on social media. The implementation of the predictability principle is carried out by giving a uniformed website appearance and format. The principle of control is applied by utilising communication technology such as smartphones, search engines, and social media analytics programme in the process of journalistic work.